Recent advances of "soft" bio-polycarbonate plastics from carbon dioxide and renewable bio-feedstocks via straightforward and innovative routes. (December 2019) - Cui, Shaoqing; Borgemenke, Joshua; Liu, Zhe; Li, Yebo
Graphical abstract: Highlights: Bio-based polycarbonates directly converted from CO2 and bio-based feedstocks. Bio-based polycarbonates showing attractive "soft" mechanical properties. Bio-based epoxide monomers possessing long backbone chains. New platform to convert CO2 and agro-/industrial wastes to value-added bio-products. Challenges and engineering perspective are proposed for future development. Abstract: As one of the main plastic resin types, polycarbonate-based plastics play an important role in manufacturing and wide applications. However, with increasing awareness of environmental challenges related to petroleum-based polycarbonates, demand for production of bio-based polycarbonates from carbon dioxide (CO2 ) and renewable feedstocks has attracted significant attention in view of green chemistry and sustainable development. This present review highlights recent advances in the efficient conversion of CO2 and bio-based feedstocks to value-added bio-based polycarbonates with attractive properties. Specifically, an emphasis has been put to renewable bio-based feedstocks that provide bio-based epoxides with long chains, resulting in "soft" bio-polycarbonate materials via innovative and efficient synthetic pathways. These bio-based feedstocks, including plant oils, industrial byproducts (crude glycerol) and pure fatty acids as the comparison, trigger new platform to fully take advantage of CO2 and agricultural or industrial byproducts to bio-degradable polycarbonate plastics. But, some challenges regarding comparable mechanical properties and scale-up do exist. A comprehensive overview of epoxide properties, synthetic mechanism, and state of the art of bio-based polycarbonates from designed bio-based feedstocks are discussed in details. Additionally, an outlook of further engineering consideration has been touched providing insights and forecasts for developing value-added bio-products from CO2 and bio-based feedstocks.